THE IMPACT OF PRISON DISPLACEMENT ON APARTMENT SALE PRICE (A CASE STUDY FOR YEONGDENGPO OLD PRISON, SEOUL) - Sohn, Chul; Trimarstuti, Jeki (University Of Technology Yogyakarta, 2019)
Locally unwanted land uses (LULUs) impact differently over time. Prison is one of the LULUs that may influence nearby real estate prices. Yeongdengpo Old Prison is located at the center of Seoul, the capital city of South Korea. After the fast urbanization of Seoul, nowadays that area is covered by apartments with more than 10 stories. Therefore, city planners of Seoul designed a new prison location outside the Seoul city. We assessed the apartment prices before the rumor of prison relocation, during the rumor stage, after the public announcement and after the relocation happens. We used average price of apartment sale in 2000, constant price of apartment sales from 2006 to 2012 and the nominal price and transaction prices of apartments from April 2013 to June 2013 for GIS analysis to determine distance effect of the prison within 500m. We used hedonic regression model to test the effects of area, age, unit, and distance from prison of apartments to its prices. The effect of relocation was not big enough compare to the first announcement of the relocation. Therefore, the distance premium mostly effected by the first public announcement of the relocation and the effect gradually diminished until the relocation happen.